Three-decade spatial patterns in surface mass balance of the Nivlisen Ice Shelf, central Dronning Maud Land, East Antarctica - Pratap, Bhanu; Dey, Rahul; Matsuoka, Kenichi; Moholdt, Geir; Lindbäck, Katrin; Goel, Vikram; Laluraj, C M; Thamban, Meloth (Journal of Glaciology, 2022)
The coastal Droning Maud Land in East Antarctica is characterized by small ice shelves with numbers of promontories and locally grounded isles, both called ice rises. These ice rises are typically dome-shaped and surface elevations are hundreds of meters above the surrounding ice shelves, which cause strong orographic effects on surface mass balance (SMB). We conducted shallow ice-penetrating radar sounding to visualize firn stratigraphy in the top 35 m over ~400 km of profiles across the Nivlisen Ice Shelf, and in a grid pattern over two adjacent ice rises (Djupranen and Leningradkollen). We tracked six reflectors (isochrones) and dated them using two ice cores taken at the ice rise summits, from which SMB over six periods in the past three decades was retrieved. The overall SMB pattern across the ice shelf remained similar for all periods; however, the eastwest contrast in SMB varies by a factor of 1.5–2 between the Leningradkollen and Djupranen grounding lines. The SMB patterns over the ice rises are more varied owing to complex interactions between topography, snowfall and wind. We use our results to evaluate the regional climate model RACMO2.3p2 in terms of the spatial SMB distribution and temporal changes over the ice shelf and ice rises at regional scale.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi; isshelf; stratigrafi

Evolution of Derwael Ice Rise in Dronning Maud Land, Antarctica, over the last millennia - Drews, Reinhard; Matsuoka, Kenichi; Martín, Carlos; Callens, D; Bergeot, Nicolas; Pattyn, Frank (Journal of Geophysical Research: Earth Surface, 2015)
Ice rises situated in the ice-shelf belt around Antarctica have a spatially confined flow regime with local ice divides. Beneath the divides, ice stratigraphy often develops arches with amplitudes that record the divide's horizontal residence time and surface elevation changes. To investigate the evolution of Derwael Ice Rise, Dronning Maud Land, Antarctica, we combine radar and GPS data from three consecutive surveys, with a two-dimensional, full Stokes, thermomechanically coupled, transient ice-flow model. We find that the surface mass balance (SMB) is higher on the upwind and lower on the downwind slopes. Near the crest, the SMB is anomalously low and causes arches to form in the shallow stratigraphy, observable by radar. In deeper ice, arches are consequently imprinted by both SMB and ice rheology (Raymond effect). The data show how arch amplitudes decrease as along-ridge slope increases, emphasizing that the lateral positioning of radar cross sections is important for the arch interpretation. Using the model with three rheologies (isotropic with n=3,4.5 and anisotropic with n=3), we show that Derwael Ice Rise is close to steady state but is best explained using ice anisotropy and moderate thinning. Our preferred, albeit not unique, scenario suggests that the ice divide has existed for at least 5000 years and lowered at approximately 0.03 m a−1 over the last 3400 years. Independent of the specific thinning scenario, our modeling suggests that Derwael Ice Rise has exhibited a local flow regime at least since the Mid-Holocene.
Keywords: Dronning Maud Land; fjernmåling; glasiologi; innlandsis; isbreer; stratigrafi

Reassembling Gondwana: A new high quality constraint from vibroseis exploration of the sub-ice shelf geology of the East Antarctic continental margin - Kristoffersen, Yngve; Hofstede, Coen; Diez, Anja; Blenkner, Richard; Lambrecht, Astrid; Mayer, Christoph; Eisen, Olaf (Journal of Geophysical Research: Solid Earth, 2014)
The breakup of Gondwana is manifested by coeval early Jurassic Karoo magmatism in South Africa and East Antarctica. In South Africa, the large volumes of volcanic rocks of the adjoining Lebombo and Mwenetzi-Save monoclines represent a volcanic rift margin, and in East Antarctica, a corresponding feature, the Explora Wedge is buried below sediments and floating ice shelves on the continental margin of Dronning Maud Land. We use the seismic vibrator source to explore the sub-ice geology in Antarctica, and the new seismic reflection and available regional aeromagnetic data enable us to outline a dogleg landward extent of the Explora Wedge in Dronning Maud Land. The congruent inboard wedge geometries on the two continents define a high quality constraint, which facilitate for the first time, a geologically consistent and tight reconstruction of Africa relative to East Antarctica within Gondwana. The uncertainties in correlations of major geological features (mobile belts) from one continent to the other may now be of the order of ten's of kilometers rather than hundreds of kilometers.
Keywords: Antarktis; geofysikk; geologi; kontinentalmargin; seismologi; stratigrafi

Glaciomarine sediments and suspended particulate matter, Weddell Sea Shelf, Antarctica - Elverhøi, Anders; Roaldset, Elen (Polar Research, 2010)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; sedimentologi; stratigrafi

Crustal structure and tectonic provinces of the Riiser-Larsen Sea area (East Antarctica): results of geophysical studies - Leitchenkov, German; Guseva, J; Gandyukhin, V; Grikurov, G; Kristoffersen, Yngve; Sand, M; Golynsky, A; Aleshkova, N (Marine Geophysical Researches, 2008)
Keywords: Sørishavet; kontinentalmargin; marin geofysikk; seismologi; stratigrafi

A seismo-stratigraphic analysis of glaciomarine deposits in the eastern Riiser-Larsen Sea (Antarctica) - Solli, Kenneth; Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J; Gandjukhin, V (Marine Geophysical Researches, 2007)
Keywords: Sørishavet; innlandsis; kontinentalsokkel; seismologi; stratigrafi

Ice core melt features in relation to Antarctic coastal climate - Kaczmarska, Marzena; Isaksson, Elisabeth; Karlöf, Lars; Brandt, Ola; Winther, Jan-Gunnar; van de Wal, Roderik S W; van den Broeke, Michiel; Johnsen, Sigfus J (Antarctic Science, 2006)
Measurement of light intensity transmission was carried out on an ice core S100 from coastal Dronning Maud Land (DML). Ice lenses were observed in digital pictures of the core and recorded as peaks in the light transmittance record. The frequency of ice layer occurrence was compared with climate proxy data (e.g. oxygen isotopes), annual accumulation rate derived from the same ice core, and available meteorological data from coastal stations in DML. The mean annual frequency of melting events remains constant for the last ∼150 years. However, fewer melting features are visible at depths corresponding to approximately 1890–1930 AD and the number of ice lenses increases again after 1930 AD. Most years during this period have negative summer temperature anomalies and positive annual accumulation anomalies. The increase in melting frequency around ∼1930 AD corresponds to the beginning of a decreasing trend in accumulation and an increasing trend in oxygen isotope record. On annual time scales, a relatively good match exists between ice layer frequencies and mean summer temperatures recorded at nearby meteorological stations (Novolazarevskaya, Sanae, Syowa and Halley) only for some years. There is a poor agreement between melt feature frequencies and oxygen isotope records on longer time scales. Melt layer frequency proved difficult to explain with standard climate data and ice core derived proxies. These results suggest a local character for the melt events and a strong influence of surface topography.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi; klima; stratigrafi

Physical properties and stratigraphy of surface snow in western Dronning Maud Land, Antarctica - Kärkäs, Eija; Martma, Tõnu; Sonninen, Eloni (Polar Research, 2005)
Information about the spatial variations of snow properties and of annual accumulation on ice sheets is important if we are to understand the results obtained from ice cores, satellite remote sensing data and changes in climate patterns. The layer structure and spatial variations of physical properties of surface snow in western Dronning Maud Land were analysed during the austral summers 1999/2000, 2000/01 and 2003/04 in fi ve different snow zones. The measurements were performed in shallow (1 - 2 m) snow pits along a transect extending 350 km from the seaward edge of the ice shelf to the polar plateau. These pits covered at least the last annual accumulation and ranged in elevation from near sea level to 2500 m a.s.l. The ?18O values and accumulation rates had a good linear correlation with the distance from the coast. The mean accumulation on the ice shelf was 312 ± 28 mm water equivalent (w.e.); in the coastal region it was 215 ± 43 mm w.e. and on the polar plateau it was 92 ± 25 mm w.e. The mean annual conductivity and grain size values decreased exponentially with increasing distance from the ice edge, by 48 %/100 km and 18 %/100 km respectively. The mean grain size varied between 1.5 and 1.8 mm. Depth hoar layers were a common phenomenon, especially under thin ice crusts, and were associated with low dielectric constant values.
Keywords: Dronning Maud Land; geofysikk; geologi; havnivå; innlandsis; klimatologi; miljøendringer; overflatesnø; snø akkumulasjon; stratigrafi

Improved Seismic Stratigraphy of the Mesozoic Weddell Sea - Rogenhagen, Johannes; Jokat, Wilfried; Hinz, Karl; Kristoffersen, Yngve (Marine Geophysical Researches, 2004)
We present a compilation of more than 45,000 km of multichannel seismic data acquired in the last three decades in the Weddell Sea. In accordance with recent tectonic models and available drillhole information, a consistent stratigraphic model for depositional units W1–W5 is set up. In conjunction with existing aeromagnetic data, a chronostratigraphic timetable is compiled and units W1.5, W2 and W3 are tentatively dated to have ages of between 136 Ma and 114 Ma. The age of W3 is not well constrained, but might be younger than 114 Ma. The data indicate that the thickest sediments are present in the western and southern Weddell Sea. These areas formed the earliest basins in the Weddell Sea and so the distribution of Mesozoic sediments is in accordance with the tectonic development of the ocean basin. In terms of Cenozoic glacial sediments, the largest depocenters are situated in front of the Filchner–Ronne Shelf, i.e. at the Crary Fan, with a thickness of up to 3 km.
Keywords: Antarktis; Weddellhavet; geofysikk; oseanografi; seismologi; stratigrafi; tektonikk

Effort explores 130 Million years of Antarctic paleoenvironment - Kristoffersen, Yngve; Goodwin, Ian D; Cooper, Alan K (Eos, Transactions American Geophysical Union, 2000)
Antarctic climate history has been dominated by events and turning points with causes that are poorly understood. To fill the gaps in our knowledges new effort is underway in the international geologic community to acquire and coordinate the circum-Antarctic geologic data needed to derive and model paleoenvironments of the past 130 m.y. The effort, which focuses principally on using shallow (<100 m) stratigraphic drilling and coring to acquire the geologic data, is being led by the Antarctic Offshore Stratigraphy Project (ANTOSTRAT), a group that works under the aegis of the Scientific Committee on Antarctic Research (SCAR). About 40 scientists from 12 countries met this past summer in Wellington, New Zealand, at an ANTOSTRAT meeting to discuss strategies for implementing the desired paleoenvironmental field and modeling studies. The meeting was held in conjunction with the 8th International Symposium on Antarctic Earth Sciences.
Keywords: Antarktis; geologi; geovitenskap; klimatologi; paleontologi; stratigrafi

Pilot shallow drilling on the continental shelf, Dronning Maud Land, Antarctica - Kristoffersen, Yngve; Strand, Kari; Vorren, Tore; Harwood, Dave; Webb, Peter (Antarctic Science, 2000)
A light, mining drill rig deployed from the stern of a research vessel has been used to carry out shallow drilling in 212 m water depth on the continental shelf in the eastern Weddell Sea. Penetration was 15 m below the seabed with 18% recovery in the 31 hours available for the experiment. The recovered glacigenic sediments are predominantly volcanic material of basaltic and andesitic composition with petrological characteristics and age similar to the continental flood basalts exposed in Vestfjella, about 130 km upstream from the drill site. The sediments include a reworked marine Miocene diatom flora. The material documents oscillations of the East Antarctic Ice Sheet over the past 30 ka. The lowermost diamicton probably represents a deformation till, and the grounding line retreated past the drill site 30 km from the shelf edge about 30 kyr BP. A readvance occurred during the Late Wisconsin Glacial Maximum. Assuming a reservoir correction of 1300 yr, marine conditions existed at the site between 10.1-7 kyr BP, and later at least between 2.8 and 2.5 kyr BP. The stratigraphy at the site has been disturbed by iceberg ploughing and/or contact between the ice shelf and the sea floor during local advances after 2.5 kyr BP.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; Weddellhavet; geokjemi; geologi; glasiologi; havbunnen; innlandsis; isshelf; kontinentalsokkel; stratigrafi

Present-day glaciation in the South Shetland Islands - Orheim, Olav; Govorukha, Leonid Sergeevich (Annals of Glaciology, 1982)
Publisher: Cambridge University Press
Keywords: Antarktis; firnsnø; forskning; glasiologi; isbreer; stratigrafi; vulkaner

Evidence for a late Wisconsin glaciation of the Weddell Sea - Elverhøi, Anders (Nature, 1981)
Keywords: Sørishavet; Weddellhavet; forskning; glasiologi; sedimentologi; stratigrafi

Physical characteristics and life expectancy of tabular Antarctic icebergs - Orheim, Olav (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; isberg; isfjell; isfront; isshelf; kalving; stratigrafi

Studies of surface snow at Plateau station - Lunde, Torbjørn (Antarctic Journal of the United States, 1968)
Keywords: Dronning Maud Land; ekspedisjoner; firnsnø; forskning; glasiologi; metamorfologi; morfologi; snø; stratigrafi

Studies of surface snow at Plateau Station - Orheim, Olav (Antarctic Journal of the United States, 1968)
Keywords: Dronning Maud Land; glasiologi; snø; stratigrafi